Individual Daily and Seasonal Activity Patterns in Fox Squirrels (Sciurus niger) Quantified by Temperature-Sensitive Data Loggers - Wassmer, Thomas; Refinetti, Roberto (Frontiers in Ecology and Evolution, 2019)
Almost all publications on the activity of tree squirrels have reported average patterns for the observed group or population and provided little information about the variability of these patterns in individual animals. As natural selection operates mainly on the level of individual animals, detailed data about the everyday life of single individuals and field data of high complexity are needed. This study provides low disturbance continuous recording of the diurnal/circadian activity cycle of individual fox squirrels (Sciurus niger) in a natural setting, which allowed us to document the intra-individual and inter-individual pattern variation over the seasons. The daily onsets and offsets of activity were inferred from recordings of skin temperature using iButtons attached to the necks of 14 individual squirrels over almost four years resulting in 25 continuous records totaling 1353 days. All squirrels were clearly diurnal but varied greatly in the number of daily activity bouts showing predominantly unimodal and bimodal patterns. Variations in activity patterns were related mostly to the seasons, followed by the inter-individual variability between squirrels. Fox squirrels spent 66-68% of the day in their nests in spring, summer and fall, and 77% in winter. In the same season, individual squirrels exited their nests at about the same time every morning. In summer, they left their nests about 3 hours earlier in the morning than in winter. The timing of first exits was significantly correlated with the number of daily nest exits and total out-of-nest time (ONT), and both variables were significantly correlated with both photoperiod and daily maximum temperature. Squirrels studied simultaneously showed substantial day-to-day variability in both number of daily exits and total ONT that either matched or exceeded the inter-individual variability. Many squirrels left their nests occasionally during the night, while about half occasionally spent entire nights outside an insulated nest. The timing of nest entries and exits, the modality of the activity pattern, the daily proportion of rest, and the occurrence of activity during the typically inactive time of the activity cycle are all aspects of an animal’s activity pattern. They should therefore receive more attention for the characterization of species-specific behavior.